De novo Transcriptome Sequencing Coupled With Co-expression Analysis Reveal the Transcriptional Regulation of Key Genes Involved in the Formation of Active Ingredients in Peucedanum praeruptorum Dunn Under Bolting Period - Song, Cheng; Li, Xiaoli; Jia, Bin; Liu, Li; Ou, Jinmei; Han, Bangxing (Frontiers in Genetics, 2021)
Peucedanum praeruptorum Dunn is a perennial and one-off flowering plant of the Peucedanum genus in Umbelliferae. The cultivated P. praeruptorum Dunn usually grows nutritionally in the first year and then moves into the reproductive growth in the second year. The lignification of the roots caused by bolting leads to the quality decline of crude materials. Since most of the previous studies have dealt with coumarins biosynthesis and identification of functional genes in P. praeruptorum, the scientific connotation of the inability that the bolted P. praeruptorum can not be used medically is still unclear. Here, we employed a transcriptome sequencing combined with co-expression analysis to unearth the regulation mechanism of key genes related to coumarins synthesis in pre- and post-bolting period, and to explore the mechanisms underlying the effects of bolting on the formation and transport of coumarins between the annual and biennial plants. Six cDNA libraries were constructed and the transcripts were sequenced and assembled by Illumina Hiseq platform. A total of 336,505 unigenes were obtained from 824,129 un-redundancy spliced transcripts. 114,488 unigene were annotated to the NCBI nr database. 119,017 and 10,475 unigene were aligned to Gene Ontology (GO) functional groups and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. Differential expression analysis screened out a series of up-regulated and down regulated genes related to the phenylpropanoid pathway. The heatmap clustering showed the similar expression patterns were both observed in groups C vs D and groups C vs F. The WGCNA-based co-expression were performed to elucidate the module and traits relationship to unearth important genes related to bolting process. Seven pivotal modules on the KEGG functional annotations suggested these genes were mainly enriched in the process of plant-pathogen interaction, plant hormone signal transduction, MAPK signaling pathway, α-linolenic acid metabolism, circadian rhythm, and phenylpropanoid pathway. Further analysis provided clues that the key genes of the phenylpropanoid pathway, the ABC transporters, the apoptosis-related and circadian rhythm regulatory genes may played pivotal roles in regulating bolting signaling, biosynthesis and transportation of coumarins.